2009
DOI: 10.1590/s0103-50532009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the interaction between doxorubicin and Deoxyribonucleic acid with the use of methylene blue as a probe

Abstract: Neste trabalho, a interação de doxorrubicina com DNA (obtido de timo de bezerro) em fita dupla foi investigada através de técnicas de espectrofotometria UV-Vis, voltametria e espectrofluorometria, usando azul de metrileno (MB) como marcador. O comportamento voltamétrico da doxorrubicina foi investigado em eletrodo de carbono vítreo usando voltametria de pulso diferencial. A doxorrubicina é reduzida, produzindo um pico de redução. Os dois estudos, espectrofotometria UV-Vis e voltametria de pulso diferencial, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 30 publications
5
32
0
Order By: Relevance
“…The apparent binding constant obtained from double reciprocal plot (see (6), Figure 5) was (1.66 ± 0.12) × 10 4 M −1 (Table 2) indicating that there was excellent agreement between the two approaches. A previous study by Hajian and coworkers [42] showed apparent binding constant for the interaction of doxorubicin hydrochloride-CT DNA in phosphate buffer at pH 7.4 as agreement with our results. The slight deviation between the previous and present results may be due to different types of measurements and different reaction media in the two studies.…”
Section: Interaction Of Doxorubicinsupporting
confidence: 93%
“…The apparent binding constant obtained from double reciprocal plot (see (6), Figure 5) was (1.66 ± 0.12) × 10 4 M −1 (Table 2) indicating that there was excellent agreement between the two approaches. A previous study by Hajian and coworkers [42] showed apparent binding constant for the interaction of doxorubicin hydrochloride-CT DNA in phosphate buffer at pH 7.4 as agreement with our results. The slight deviation between the previous and present results may be due to different types of measurements and different reaction media in the two studies.…”
Section: Interaction Of Doxorubicinsupporting
confidence: 93%
“…Because it is well established that if there is a shift towards to negative potential, interaction between DNA and regarding complex is mainly electrostatic since electrostatic interaction between DNA and the complexes makes reduction at the surface more difficult. However, in this study, the peak potential appears at the more positive values in the presence of DNA, indicating an intercalation binding mode [32][33][34][35][36][37][38]. Owing to the fact that 1 and 2 possess positive charge, it is intrinsically expected that both platinum complexes have a binding affinity to dsDNA by an electrostatic interaction as previously reported for other positively charged molecules.…”
Section: Electrochemistry Of [Pt(bpy)(pip)] 2+ and [Pt(bpy)(hpip)] 2+supporting
confidence: 62%
“…It may be attributable to a compensatory adaptive response to chemical stress that is overwhelmed as the stress progresses; this has shown to be the case, for example, with diquat [11] and may well be the case for Mz and AC. The anthracyclines are known to produce anticancer effects by their intercalation into DNA to inhibit the cell cycle [12]. This is associated with nuclear swelling.…”
Section: In Vitro Drug Effectsmentioning
confidence: 99%